Análisis de las prácticas contables y su incidencia en el proceso contable de las empresas comerciales disprac y dicolaic del cantón Latacunga, provincia de Cotopaxi - Pichucho Tipanluisa, Mercy Vanessa (2017)
The research has as purpose to analyze the correct application of accounting practices in the accounting process of commercial companies DISPRAC AND DICOLAIC, Considering that since 2010 Ecuadorian companies according to Resolution No. 08.G.DSC of date 2008/12/31. Issued by the superintendence of companies indicates that the accounting principles will change from NEC to IFRS. DISPRAC and DICOLAIC entities are natural persons required to keep accounts, therefore they are not obliged to submit financial information in accordance with IFRS, however, these companies partially and voluntarily accepted the change from NEC to IFRS, from 2014. The financial information currently handled by these entities lacks adequate application of accounting practices, due to the lack of full application of IFRS for PYMES reason for which the information provided does not allow a faithful representation of the assets, liabilities, equity, income and expenses in addition to the comprehensibility and comparability of the information in the financial statements, The objective of the research is to analyze the incidence of accounting practices in the development of the accounting process of comercial companies DISPRAC and DICOLAIC, By comparing financial information that allows make timely decisions. To carry out this review, the qualitative research methodology will be applied, in order to identify the inadequate application of accounting practices within companies, in addition the use of the deductive method with which information is collected, through the application of a questionnaire that applies to accountants and managers of commercial companies. The impact of this research is focused on identifying the accounting practices that commercial companies should consider when preparing their financial statements